On the Origin of the Hydrophobic Water Gap: An X-ray Reflectivity and MD Simulation Study - Mezger, Markus; Sedlmeier, Felix; Horinek, Dominik; Reichert, Harald; Pontoni, Diego; Dosch, Helmut (Journal of the American Chemical Society, 2010)
The density deficit of water at hydrophobic interfaces, frequently called the hydrophobic gap, has been the subject of numerous experimental and theoretical studies in the past decade. Recent experiments give values for the interfacial depletion that consistently correspond to less than a monolayer of water. The main question which remained so far unanswered is its origin and the mechanisms affected by the chemistry and molecular geometry of a particular hydrophobic coating. In this work, we present a combined high-energy X-ray reflectivity and molecular dynamics simulation study of the water depletion at a perfluorinated hydrophobic interface with a spatial resolution on the molecular scale. A comparison of our experimental and computational results elucidates the underlying mechanisms that affect the extent of the interfacial depletion. The complex interplay between surface chemistry and topography precludes the existence of a direct and universal relation between the macroscopic contact angle and the nanoscopic water depletion.